Analisis Perilaku Mahasiswa Sains dan Teknologi dalam Penggunaan Smartphone (gadget) untuk Meningkatkan Prestasi Akademik - Ekie Gilang Permata; Harpito Harpito; Ismu Kusumanto; Zulmiriyanto Zulmiriyanto (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2019)
Nowadays smartphone users are increasing, including Industrial Engineering Students at UIN SUSKA Riau. The use of smartphones has a positive-negative impact so it is worth responding to as best as possible. Student behavior using smartphones varies, whether it is in line with expectations to improve academic achievement. Research knows how the behavior of students using smartphones with statistical tests, namely the test of validity, reliability and linear regression test to determine the effect of independent variables on the dependent variable (Student IP). Based on the results of the study involving 260 samples from 737 population of Industrial Engineering Students in 2018 showed a reliability value of 0.746 with 25 statements declared valid. The results of linear regression are Y=2,796+0,004X1-0,029X2+0,019X3+0,089X4+0,051X5+0,033X6+0,051X7. The most influential variable is the variable